Transitions across schools and cultures - Karabenick, Stuart A.; Urdan, Timothy C. (Bingley, U.K. : Emerald, 2012)
This volume focuses on the "Transitions" that take place at major points of potential discontinuity in students' developmental trajectories and across contexts at a given time point. The development literature, for example, has examined how children's motivation and achievement are affected by the shift from pre-school to school. And a topic that has received considerable attention in the achievement motivation literature is the transition from elementary to middle school. There is less information about the middle to high school transition. The transition from high school to college or school to work represents another important inflection point. Other transitions concern switching from one culture to another over time (e.g., immigration and acculturation), or at a given time point, such as when students shuttle between a dominant school culture and a minority home culture, or foreign students at colleges and universities who may study and socialize with other students from their home culture as well as those from the host culture.
The transition to kindergarten : fostering connections for early school success / Jennifer LoCasale-Crouch ... [et al.] -- School transitions and African American youth / Beth Kurtz-Costes, Stephanie J. Rowley -- Pathways to college : Latino youth and the transition to higher education / Pamela E. Davis-Kean, Celeste M. Mendoza, Maria Ines Susperreguy -- Engagement and disengagement during critical transitions from school to work / Katariina Salmela-Aro -- Being the new kid : implications of within-year academic transitions for motivational development in school / Gwen C. Marchand, Kayana Sanders -- Risk and resilience in adolescents' transnational school transitions : academic motivation and psychological well-being / Revathy Kumar, Nancy Seay, Jeffrey H. Warnke -- To go or not to go : the decision to pursue higher education abroad / Fani Lauermann -- Studying 'a thousand miles away' : the motivational implications of cross-cultural transitions / Dennis M. McInerney, Ronnel B. King -- Cultural transitions in higher education : individual adaptation, transformation and engagement / Simone Volet, Cheryl Jones.
Keywords: Psychology -- Education & Training; Education -- Educational Psychology; Cognition & cognitive psychology; Religion: general; Education